Comparison of Cystatin-C Based eGFR and Creatinine Based eGFR to Assess Kidney Function in Patients With Chronic Kidney Disease Stage V Undergoing Hemodialysis at RSUD Dr. Mohamad Soewandhie Surabaya - Denny Chandra; Rahajoe Imam Santoso; Mulyadi Mulyadi (International Journal Of Health Science, 2026)
Chronic kidney disease (CKD) is a global health problem with continuously increasing incidence and mortality, and accurate assessment of kidney function is essential for disease staging and clinical decision making. Estimation of glomerular filtration rate (eGFR) based on serum creatinine using the CKD-EPI 2009 equation is widely used, however it is influenced by nonrenal factors such as age, sex, and muscle mass, whereas cystatin C is considered a more stable biomarker. This observational analytic study with a cross sectional design aimed to analyze the differences and agreement between creatinine based eGFR and cystatin C based eGFR in 53 patients with stage V CKD undergoing hemodialysis at RSUD dr. Mohamad Soewandhie Surabaya prior to dialysis. Creatinine based eGFR was calculated using the CKD-EPI 2009 equation and cystatin C based eGFR using the CKD-EPI 2012 equation. Statistical analysis was performed using the Wilcoxon signed rank test and Bland Altman analysis. The Wilcoxon test showed that all paired data had positive ranks with a Z value of –6.336 and p < 0.001, indicating a statistically significant difference. Bland Altman analysis demonstrated a bias of –41.64 mL/min/1.73 m² with limits of agreement ranging from –105.14 to 21.86, indicating that the two methods are not interchangeable. In conclusion, a significant difference exists between creatinine based eGFR and cystatin C based eGFR, and these methods cannot be used interchangeably in clinical practice among patients with stage V CKD at RSUD dr. Mohamad Soewandhie Surabaya.